2005
DOI: 10.1246/bcsj.78.361
|View full text |Cite
|
Sign up to set email alerts
|

Selective Catalytic Reduction of NO by Methane over Pd Loaded on Heteropolyacids/SiO2 at Low Temperature

Abstract: Pd was loaded on heteropolyacids/SiO2, and used for the selective reduction of NO with methane in the presence of oxygen and moisture. The catalyst exhibited activity in the selective reduction of NO in the temperature range between 473 and 573 K. The temperature was significantly lower than that in the conventional catalysts, such as Pd-loaded zeolites or monolayer-type oxides. Among tested heteropolyacids, H3PW12O40 gave rise to the highest activity in the reaction. The catalytic performance was improved by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The present work focuses on the reduction of NO with H 2 (H 2 -SCR). This reaction is not as selective for N 2 as, for instance, ammonia, but it has potential technological applications due to its lower onset temperature and the fact that H 2 is readily available in exhaust streams (from the water-gas-shift reaction or from hydrocarbons) . Noble-metal-based catalysts are generally preferred for the H 2 -SCR of NO because of their high selectivity and reduced operation temperatures. , Although Rh is overall catalytically better than Pd for NO-SCRs, the lower cost, higher abundance, and low-temperature activity of Pd have made it a material of choice in industrial applications. , A vast amount of literature is available describing the conversion and selectivity of various combinations of metal catalyst, support, and reducing agent. ,, However, much less attention has been paid to the optimization of the structure and oxidation state of the active catalysts, its evolution under reaction conditions, and its influence on catalytic performance. , Nevertheless, previous work has revealed the important role of the oxidation state of metal catalysts in their activity, selectivity, and stability for NO-SCRs. For example, oxidized Rh catalysts are more active for H 2 -SCR than metallic Rh, and NO adsorption on Cu catalysts is faster on the oxidized surface, contrary to the faster adsorption reported on the reduced surfaces of other materials such as chromia or manganese oxides .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present work focuses on the reduction of NO with H 2 (H 2 -SCR). This reaction is not as selective for N 2 as, for instance, ammonia, but it has potential technological applications due to its lower onset temperature and the fact that H 2 is readily available in exhaust streams (from the water-gas-shift reaction or from hydrocarbons) . Noble-metal-based catalysts are generally preferred for the H 2 -SCR of NO because of their high selectivity and reduced operation temperatures. , Although Rh is overall catalytically better than Pd for NO-SCRs, the lower cost, higher abundance, and low-temperature activity of Pd have made it a material of choice in industrial applications. , A vast amount of literature is available describing the conversion and selectivity of various combinations of metal catalyst, support, and reducing agent. ,, However, much less attention has been paid to the optimization of the structure and oxidation state of the active catalysts, its evolution under reaction conditions, and its influence on catalytic performance. , Nevertheless, previous work has revealed the important role of the oxidation state of metal catalysts in their activity, selectivity, and stability for NO-SCRs. For example, oxidized Rh catalysts are more active for H 2 -SCR than metallic Rh, and NO adsorption on Cu catalysts is faster on the oxidized surface, contrary to the faster adsorption reported on the reduced surfaces of other materials such as chromia or manganese oxides .…”
Section: Introductionmentioning
confidence: 99%
“…4,26,29À31 However, much less attention has been paid to the optimization of the structure and oxidation state of the active catalysts, its evolution under reaction conditions, and its influence on catalytic performance. 70,71 Nevertheless, previous work has revealed the important role of the oxidation state of metal catalysts in their activity, selectivity, and stability for NO-SCRs. For example, oxidized Rh catalysts are more active for H 2 -SCR than metallic Rh, 72 and NO adsorption on Cu catalysts is faster on the oxidized surface, contrary to the faster adsorption reported on the reduced surfaces of other materials such as chromia or manganese oxides.…”
mentioning
confidence: 99%
“…The catalyst exhibited high activity for NO reduction when branched aromatic hydrocarbons, such as toluene and xylene, were used as reductants. 13,14 Several authors have reported the deactivation of V 2 O 5 -WO 3 /TiO 2 catalysts by alkaline metals in biomass fired power plants. [15][16][17] Most conclude that poisonous elements (e.g.…”
Section: Introductionmentioning
confidence: 99%